Loss of PFKFB4 induces cell death in mitotically arrested ovarian cancer cells - Taylor, C; Mannion, D; Miranda, F; Karaminejadranjbar, M; Herrero-Gonzalez, S; Hellner, K; Zheng, Y; Bartholomeusz, G; Bast, R; Ahmed, A (Impact Journals, 2017)
Taxanes represent some of the most commonly used chemotherapeutic agents for ovarian cancer treatment. However, they are only effective in approximately 40% of patients. Novel therapeutic strategies are required to potentiate their effect and improve patient outcome. A hallmark of many cancers is the constitutive activation of the PI3K/AKT pathway, which drives cell survival and metabolism. We discovered a striking decrease in AKT activity coupled with a significant reduction in glucose 6-phosphate and ATP levels during mitotic arrest in the majority of ovarian cancer cell lines tested, indicating a potential metabolic vulnerability. A high-content siRNA screen to detect novel metabolic targets in mitotically arrested ovarian cancer cells identified the glycolytic enzyme PFKFB4. PFKFB4 depletion increased caspase 3/7 activity, and levels of reactive oxygen species only in mitotically arrested cells, and significantly enhanced mitotic cell death after paclitaxel treatment. Depletion of PFKFB3 demonstrated a similar phenotype. The observation that some ovarian cancer cells lose AKT activity during mitotic arrest and become vulnerable to metabolic targeting is a new concept in cancer therapy. Thus, combining mitotic-targeted therapies with glycolytic inhibitors may act to potentiate the effects of antimitotics in ovarian cancer through mitosis-specific cell death.